Antifungal mechanism of cinnamaldehyde and citral combination against Penicillium expansum based on FT-IR fingerprint, plasma membrane, oxidative stress and volatile profile. Issue 11 (5th February 2018) - Wang, Yuan; Feng, Kewei; Yang, Haihua; Yuan, Yahong; Yue, Tianli
Abstract : Cinnamaldehyde (Cin) and citral (Cit) have been studied as antimicrobial agents and natural preservatives, but their action modes are controversial, and the knowledge of their antifungal mechanism against P. expansum is still incomplete. Abstract : Cinnamaldehyde (Cin) and citral (Cit) have been studied as antimicrobial agents and natural preservatives, but their action modes are controversial, and the knowledge of their antifungal mechanism against P. expansum is still incomplete. The present study was conducted to evaluate the antifungal mechanism of the combination of Cin and Cit (Cin/Cit) against P. expansum by observing the cellular ultrastructure, fourier transform infrared spectroscopy (FT-IR) fingerprints, plasma membrane, oxidative stress and volatile profile. Cin/Cit caused membrane invaginations, organelles and cytoplasm destruction, as shown by transmission electron microscopy (TEM) observations. The FT-IR spectra and followed principle component analysis (PCA) presented the significant differences in chemical compounds, particularly phospholipid, protein and fatty acids of cells exposed to Cin/Cit. Compared to controls, Cin/Cit induced a decrease of ergosterol by 39.40%, an increase of unsaturated fatty acid, and protein release level (3.5 times). Besides, membrane damage was further verified through the reduction of the membrane integrity by using a flow cytometer. Moreover, the increase of malondialdehyde (MDA) (40.09%) and reactive oxygen species (ROS) accumulation indicated an induction of oxidative stress in cells by Cin/Cit. To resist the unfavorable stress caused by Cin/Cit, P. expansum metabolized Cin or Cit to the predominant detoxification compounds, cinnamic alcohol, nerol, and geraniol. The alterations in volatile profile demonstrated the influences on specific metabolisms in P. expansum caused by Cin/Cit.